Performance of Sediment Microbial Fuel Cells in Generating Electricity using Fish Wastewater and Shrimp Wastewater as a Nutrient and Their Effect on Waste Quality - Alif, Alfiah; Jalil Baari, Muhamad; Febryanti, Amalyah (Publisher Cv. Inara, 2023)
Sediment Microbial Fuel Cell (MFC) is a technology that can convert chemical energy into electrical energy through the process of nutrient degradation by microbes. Sediment taken from the bottom of shrimp ponds was added as a source of microbes, while fish and shrimp wastewater were used as a source of nutrients for microbes. This study aims to measure the performance of the SMFC system on fish effluent and shrimp effluent to produce bio-electricity while reducing the waste load. The research method was experimental laboratories. The treatment given was the different types of electrodes, namely zinc-copper and aluminum-copper. In addition, 0.2 M KMnO4 electrolyte solution was used. This study consisted of four stages: the manufacture of nutrients from fish and shrimp wastewater, the manufacture of a dual chamber MFC bioreactor, the measurement of electrical values, and the analysis of waste quality. Experiments were carried out for 30 days by measuring electricity every 24 hours. The average value of electricity generated in the nutrients of fish wastewater with Zn/Cu electrodes was 0.705 V and Al/Cu was 0.472 V. Meanwhile, the average value of electricity in shrimp wastewater nutrients with Zn/Cu electrodes was 0.630 V and Al/Cu was 0.625 V. The number of colonies after adding sediment in the shrimp wastewater sample were 8.9 x 106 CFU/mL, the fish wastewater sample was 9.5 x 106 CFU/mL. It indicates the presence of microorganisms that play a role in the SMFC system